O texto literário na aula de PLE: algumas considerações e uma proposta para a didatização do conto Bibliotecas, de Valter Hugo Mãe - Ferreira, Daniel (2021)
The use of literary texts results in extremely productive strategies for foreign language classes. Its resource creates an opportunity for reflective practice on the target language-culture and, consequently, enables the training of skills that are not only linguistic but also cognitive, aesthetic, cultural, social and human (Council of Europe 2001, 2018). Based on these assumptions, this study aims to promote literary texts in Portuguese as a foreign language (PFL) learning and teaching contexts and, for that purpose, follows the problematization of some theories and practices. At the end, there is a proposal for didacticization of "Bibliotecas", a tale by Valter Hugo Mãe, as a suggestion for the introduction of literary texts in PFL classes.